Structural and Functional Characterization of Rice Yield Enhancing Genes by in Silico Approach - Goud, Chengeshpur Anjali; Bhargava, Kadthala; Sadhana, P.; Dattatray, Bichewar Nagesh; Shivani, D.; Nagamani, Gorantla (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted at Institute of Biotechnology (IBT), Rajendranagar, Hyderabad, Telangana, India in kharif, 2022 (July‒October) to characterize yield enhancing genes in rice by in Silico Approach. Increasing the rice grain yield is a major constraint to feed the present burgeoning population which is anticipated to reach nine billion by 2050. In this regard many yield enhancing genes have been characterized for improving the yield potential in rice. Present study was undertaken on eight yield enhancing genes of rice for their structural and functional characterization by in silico approach. The conserved motif sequences shared across eight yield enhancing genes were identified and their positions on the genome were reported. The Spatio-temporal expression pattern of the yield genes in different stages of rice was studied, of which Gn1a and SPL14 genes shown higher level of expression at embryo and inflorescence stages respectively. Further, the expression patterns of these genes to different hormonal exposures were recorded in which Gn1a gene showed higher level of expression to cytokinin hormone in root and shoot tissues. The structure analysis for the above eight genes recorded the exon number between 2‒10 along with their positions on the gene. Along with the protein characters of the above eight proteins, their potential interacting partners were identified, which shown their interactions to proteins controlling the flowering time, floral organ formation and regulating the grain size in rice.